Analysis of multicultural mathematics learning with RACISM and students' social attitudes - Pangaribuan, Lena Rosdiana; Dewi, Izwita; Simamora, Elmanani (International Journal of Trends in Mathematics Education Research, 2023)
Multicultural learning is a strategy for creating a learning environment and designing a learning experience that integrates culture as part of the learning process. In multicultural learning, culture becomes a method for students to transform the results of their observations into creative forms and principles of nature so that the role of students is not merely to imitate or receive information, but to act as a creation of meaning and understanding. Subjects such as Citizenship Education, Social Sciences, Natural Science, Cultural Arts and Skills are considered to contribute to multicultural learning, but mathematics subjects can also contribute. The research aimed to find out how the use of multicultural learning in mathematical learning, on flat building materials, affected students' racism and social attitudes. This is a qualitative descriptive study that uses the interview method to gather data. The results will be qualitatively analyzed. Interviews were conducted to find out how multiculturalism is integrated into learning, how knowledge construction is built through cultural influences, how prejudice reduction occurs, how equality pedagogy is implemented, how the empowerment of school culture occurs in the learning process, and how it impacts in tackling racism and social attitudes of students after using such learning.